Development and characterization of burger patty from kadios (Cajanus cajan). - Iray, Therese Dane G.
The study focused on the formulation and characterization of kadios seed burger patty. Three different formulations with varying amounts of kadios seeds to texturized vegetable protein (TVP) ratio (60%, 80%, and 100%) were subjected to rank test for preference to determine the most preferred formulation. Total ranks of the kadios seed burger patties from the three formulations showed significant differences (Kruskal Wallis Test, α = 0.05) but the product with a 100:0 kadios seed to TVP ratio was considered as the most preferred formulation because it had the lowest total rank. The kadios seed burger patty from this formulation was subjected to physicochemical and proxixmate analysis. The most preferred formulation of the kadios seed burger patty had a mean pH value of 5.97 and 0.956 for the water activity. The hardness had a mean of 0.686 N. It had a 28.07± 0.02% moisture content, 20.62± 0.52% crude fat, 2.67 ± 0.17% crude fiber, 9.86 ± 0.14% crude protein, 2.03 ± 0.08% ash and 36.32 ± 2.22% carbohydrates, all in wet basis. The kadios seed burger patty from the most preferred formulation was characterized through attribute rating test as dark brown in outer color, with moderately grainy texture, weak kadios odor, moderate kadios flavor and slightly juicy. Out of 90 respondents, 46% evaluated the product as very much liked, 30% rated it as liked a lot and 24% rated it as liked. None of the consumers disliked the product. Thus, kadios seed has a potential to replace beef in the production of burger patty.